Activation of Nicotinic Acetylcholine α7 Receptor Attenuates Progression of Monocrotaline-Induced Pulmonary Hypertension in Rats by Downregulating the NLRP3 Inflammasome - Deng, Yan; Guo, Sheng-Lan; Wei, Bin; Gao, Xing-Cui; Zhou, Ying-Chuan; Li, Jia-Quan (Frontiers in Pharmacology, 2019)
Background: Inflammation and altered immunity contribute to the development of pulmonary arterial hypertension (PH). The alpha 7 nicotinic acetylcholine receptor (7nAChR) possesses anti-inﬂammatory activities. The current study was performed to investigate the effects of a selective 7nAChR agonist, PNU-282987, on controlling a monocrotaline (MCT)-induced rat model of PH and explored the underlying mechanisms. Methods: Sprague-Dawley rats were injected with MCT and treated with PNU-282987 at the prevention (starting one week before MCT) and treatment (starting two weeks after MCT) settings. Four weeks after MCT injection, hemodynamic changes, right ventricular structure, and lung morphological features were assessed. ELISA, Western blot and qRT-PCR were performed to assess levels of inflammatory cytokines and NLRP3 (Nod-like receptor family pyrin domain-containing 3) inﬂammasome pathway in the rat lung tissues. In addition, the lung macrophage line NR8383 was used to confirm the in vivo data. Results: MCT injection produced PH in rats and downregulated α7nAChR mRNA and protein expression in rat lung tissues compared to sham controls. Pharmacological activation of 7nAChR by PNU-282987 therapy improved the rat survival rate, attenuated the development of PH as assessed by remodeling of pulmonary arterioles, reduced the right ventricular (RV) systolic pressure, and ameliorated the hypertrophy and fibrosis of the RV in rats with MCT-induced PH. The expression of TNF-α, IL-6, IL-1β, and IL-18 were downregulated in rat lung tissues, which implied that PNU-282987 therapy may help regulate inflammation. These protective effects involved the inhibition of the NLRP3 inflammasome. In vitro assays of cultured rat lung macrophages confirmed that the anti-inflammation effect of PNU-282987 therapy may contribute to the disturbance of NLRP3 inflammasome activation. Conclusion: Targeting α7nAChR with PNU-282987 could effectively prevent and treat PH with benefits for preventing ongoing inflammation in the lungs of rats with MCT-induced PH by inhibiting NLRP3 inflammasome activation.